2019
DOI: 10.1002/jaba.638
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of interventions to treat prompt dependence for children with developmental disabilities

Abstract: Prior research has examined interventions to prevent prompt dependence from occurring during the training of novel skills. Nevertheless, the relative efficacy and efficiency of different intervention procedures may be idiosyncratic across learners, suggesting the potential benefit of an individualized assessment. The purpose of the current study was to extend the literature on prompt dependence by comparing interventions for 3 participants with developmental disabilities who consistently engaged in correct res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…They rely on prompt and permission from paraprofessional. Gorgan and Kodak (2019) Compared intervention skills for participants who consistently engaged in correct responses following prompts, but not independently. Jowett et al (2012) Some video-based interventions for ASD have also reported prompt dependency.…”
Section: Aba Only Work For Children With Particular Characteristics Of Autismmentioning
confidence: 99%
“…They rely on prompt and permission from paraprofessional. Gorgan and Kodak (2019) Compared intervention skills for participants who consistently engaged in correct responses following prompts, but not independently. Jowett et al (2012) Some video-based interventions for ASD have also reported prompt dependency.…”
Section: Aba Only Work For Children With Particular Characteristics Of Autismmentioning
confidence: 99%
“…Although Clare engaged in some correct responses during this probe, her responding did not increase. Therefore, based on research on prompt dependence (Gorgan & Kodak, 2019 ), we extended the response interval to 10 s. However, she did not emit more correct responses. Clare may have emitted more correct responses had we implemented differential reinforcement earlier, without the long history of probes under extinction conditions (i.e., Brenna in Petursdottir et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Clare was not emitting vocal responses reliably when we added differential reinforcement; therefore, we made a final modification to increase the response interval (Gorgan & Kodak, 2019 ). We hypothesized that an extended response interval would increase the probability of vocalizations, if they were acquired under relevant sources of control, to end the probe session more quickly.…”
Section: Methodsmentioning
confidence: 99%
“…Based on Gorgan and Kodak (2019), we also modified generalization probes for Sophie by extending the response time to 10 s due to long latencies to respond or high number of no responses during probe sessions. Nevertheless, her responding did not change with this modification, and we returned to a 5-s response interval after 7 sessions.…”
Section: Extended-response Intervalmentioning
confidence: 99%